Important insight into electron transfer in single-molecule junctions based on redox metalloproteins from transition voltage spectroscopy - Bâldea, Ioan (The journal of physical chemistry. C, Energy, materials, and catalysis, 2013)
In a recent experimental work, results of the first transition voltage spectroscopy (TVS) investigation on azurin have been reported. This forms a great case to better understand the electron transfer through bacterial redox metalloproteins, a process of fundamental importance from chemical, physical, and biological perspectives, and of practical importance for nano(bio)electronics. In the present paper we challenge the tentative interpretation put forward in the aforementioned experimental study and propose a different theoretical interpretation. To explain the experimental TVS data, we adopt an extended Newns-Anderson framework, whose accuracy and robustness is demonstrated. We show that that this framework clearly meets the need to obtain a consistent description across experiments. Most importantly, the presently proposed theoretical approach permits unraveling novel aspects on the impact of the electrochemical scanning microscope environment on the charge transport through single-(bio)molecule junctions based on redox units. The usefulness of TVS as a versatile method of investigation, also able to provide important insight into the charge transport through metalloproteins, is emphasized.
Gesehen am 01.12.2020